IMMUNOPROPHYLAXIS OF CANINE PARVOVIRAL ENTERITIS - A. V. Shatalov; S. P. Dannikov; A. N. Kononov; V. S. Skripkin (Ветеринария сегодня)
Data on the specifcity of the development of post-vaccination immunity against parvovirus enteritis agent in dogs are summarized and analyzed in the review. The publications were searched for using the following bibliographical and reference databases: Russian Science Citation Index (RSCI), Scopus, Web of Science, Agris, PubMed, as well as Google Scholar search system and the electronic library of theses of the Russian State Library (RSL). Triple vaccination of puppies was found to be the most eﬀective, therewith the puppies shall be last vaccinated at the age of 16-weeks or older. Where necessary, vaccination of 4-week-old puppies and pregnant dogs is allowed. After immunization, the rates of increase in anti-canine parvovirus enteritis antibody titre do not depend on the sex of dogs or vaccine type but can vary depending on age, body weight and the presence of maternal antibodies. The titres of maternal antibodies against canine parvovirus type 2 in newborn puppies demonstrate broad individual invariance. The use of immunomodulators as adjuvants in vaccine composition is proved to be eﬀective to maintain the high titre of antibodies against canine parvovirus type 2 in the post-vaccination period, and the modern DNA-vaccine is a reasonable alternative to conventional vaccination. The probability of adverse reactions resulting from the administration of a combined vaccine containing canine parvovirus enteritis agent antigen is 3.8%; the predisposing risk factors are the following: neutering, low body weight and the age of less than 9 months old. Contemporary vaccines based on NL-35-D CPV-2 strain confer the full protection from other virulent strains of canine parvovirus type 2.